Assessment of effectiveness of emerging construction contractor development programmes in Ngaka Modiri Molema. - Mudhenge, Tawedzegwa (North-West University (South Africa), 2019)
The study investigated the effectiveness of Contractor Development Programmes among the entrepreneurs in the Ngaka Modiri Molema District Municipality in the North West Province of South Africa. The intentions were to identify whether the programme is effective or not and if not effective identify challenges, and propose solutions for the obstacles. The investigation is conducted through an evaluation of Contractors in the North West province using construction project implemented by government organisations in the North Pest Province in South Africa. This research considers the following factors in determining the effectiveness of the CDP: technical, financial and managerial training that the contractors received through the programme, the provision of relevant work experience for the duration of the programme as well as an increase in the contractor's CIDB grading after exiting the programme. The research adopted both a qualitative and quantitative research design, and in-depth interviews were used to gather data from the participants, SMMEs owners and managers in the Ngaka Modiri Molema, who were the target population. Emerging construction contractors contribute to the backbone of the South African economy, because of their importance in employment creation and value reorientation. The objective of this study will be to establish a benchmark to identify whether government policies to implement Contractor Development Programmes of SMMEs in South Africa are effective or need to be developed. The extensive literature review compiled from various articles and the field survey conducted on various SMMEs were used as the methodology. Questionnaires and random sampling were used as field survey instruments. It was found from literature that there are various obstacles in the implementation of Emerging Contractors. Among the list of the challenges are lack of finance, training and business skills, and unethical conduct amongst some of the stakeholders; these were indicated in the literature review and confirmed by field survey. The results will make contribution for developments to the problems faced by emerging construction companies in South Africa. That will give an indication to the government for in-depth research into departmental weaknesses and policy issues regarding implementation of the policy in South Africa. The findings imply that, to improve the growth and competitiveness of SMMEs, the obstacles named above have to be resolved. The research has contributed to the enhancement of understanding the programme to empower black people by establishing the core issues affecting the operations of SMMEs in South Africa. The North West Government, through its sister department, the Department of Public Works and the IDT has embarked on a positive programme for training Emerging Contractors that would make their development very effective and turn them into sustainable business enterprises. The programme will be assessed to measure its effectiveness in grooming Emerging Contractors into established contractors in the construction industry. The study further analyses the overall approach followed in implementing CDPs and emphasises some key considerations relating to the implementation approach. More importantly, the study highlights that the lack of emphasis on technical competence in terms of qualification and experience is one of the underlying shortcomings of CDPs. In conclusion, the research found that there is a need to review policies and procedures relating to CDPs.
MBA, North-West University, Mafikeng Campus
Keywords: SMME; CIDB; training and mentorship; small contractor development; contractor development programme (CDP)